Pension reforms and women retirement plans - Tito Boeri; Agar Brugiavini (Institute for the Study of Labor (IZA), 2008)
We analyse the effects of pension reforms on the planned retirement age of women by exploiting within country variation in pension wealth across cohorts of workers in Italy after the Amato and Dini reforms of the early 1990s, which introduced a Notionally Defined Contribution (NDC) method for calculating pension benefits. The effect of the change in the pension regime on retirement decisions is affected by the presence of gaps in careers of women. Binding constraints related to eligibility to pensions indeed reduce the responsiveness of women to changes in pension rules. This explains why, contrary to a priori expectations, men are often found to be more reactive than women to changes in pension rules.
urn:nbn:de:101:1-20081127504
Keywords: J14; 330; Pensions; social security wealth and accrual; gaps in careers; Rentenreform; Frauenerwerbstätigkeit; Altersgrenze; Erwerbsverlauf; Italien